Dinamika Psikologis pada Perempuan yang Mengalami Post Traumatic Stress Disorder Akibat Kekerasan Seksual Keluarga - Ida Ayu Ketut Julya Arcani; Tri Kurniati Ambarini (Universitas Kristen Maranatha, 2022)
Family sexual violence is a crucial topic to talk about since it causes victims to suffer traumatic experience and has lasting ramifications that affect their life, one of which is that it may result in Post-Traumatic Stress Disorder (PTSD). Family sexual assault cases are rarely reported by the victim or his family, making it unlikely that the victim would obtain the proper medical and legal care. This study, which is a single case study, examines the psychological dynamics of women who suffer from posttraumatic stress disorder as a result of familial sexual violence. The findings showed that victims of sexual violence experienced emotional hurdles and little social assistance from their families and places of employment. This makes the participants' situation worse, especially when it comes to forming social connections. These results suggest that in order for survivors of sexual assault to feel safer and more in control, there is a need for increased social rehabilitation and counseling.